KEPASTIAN HUKUM PENERAPAN ASAS FIRST TO FILE PADA MEREK DAGANG DI INDONESIA (STUDI KASUS PUTUSAN PENGADILAN NO.2/PDT.SUS.HKI.MEREK/2022/PN.NIAGA.SBY) - Muhammad Syahrul Maulana; Christine S.T. Kansil (LPPM Universitas Ekasakti Padang, 2023)
Ms.Glow and Ps.Glow where the product or brand name and type of product or brand and type of product belonging to Ms.Glow almost resemble Ps.Glow. In this case it is known that the first to file principle has not been implemented. Protection of the rights to a new mark will be obtained after the new mark will be obtained after the mark is registered, this is in accordance with the provisions contained in Article 3 of Law Number 20 of 2016 concerning Marks and Geographical Indications. in the form of preventive legal protection or repressive legal protection. Therefore the aims of this study are: (1) To find out the legal certainty of the application of asar first to file on trademarks in Indonesia (2) To find out the responsibility of the Directorate General of Intellectual Property Rights for the application of the first to file principle in trademark registration in Indonesia. To achieve this goal, this research was conducted using normative juridical methods. The collected legal materials will be comprehensively reviewed and analyzed deductively with a systematic presentation.